If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + -5) + 7x = 3x + 35 Reorder the terms: 3(-5 + 2x) + 7x = 3x + 35 (-5 * 3 + 2x * 3) + 7x = 3x + 35 (-15 + 6x) + 7x = 3x + 35 Combine like terms: 6x + 7x = 13x -15 + 13x = 3x + 35 Reorder the terms: -15 + 13x = 35 + 3x Solving -15 + 13x = 35 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -15 + 13x + -3x = 35 + 3x + -3x Combine like terms: 13x + -3x = 10x -15 + 10x = 35 + 3x + -3x Combine like terms: 3x + -3x = 0 -15 + 10x = 35 + 0 -15 + 10x = 35 Add '15' to each side of the equation. -15 + 15 + 10x = 35 + 15 Combine like terms: -15 + 15 = 0 0 + 10x = 35 + 15 10x = 35 + 15 Combine like terms: 35 + 15 = 50 10x = 50 Divide each side by '10'. x = 5 Simplifying x = 5
| 3/4x-2 | | -5x^2+4x=91 | | 1.2c+2.6c=4.55 | | 2/7(x-5/4)=-1/7 | | -3(4x+5)=-63 | | 5(x-9)=2(x+7) | | T-6=10 | | H=-16t^2+38t+104 | | 10x=4-(-16) | | 2x-4n=7-n | | ax+bx-9=-10 | | 18xsquared-6x-8= | | 275000.00x=13000.00+25000.00x | | 4/7x=26 | | 2(5x)+3x=7 | | 3(x+8)=x+12 | | 2x-4n=18-n | | -3y-5(y+4)=4 | | 7/3x-5 | | 2(9-2x)=26 | | 24x+12=63 | | 143=11S+11 | | B=17-14 | | 12-9x=4-5x | | 2x-2x=9 | | 4B-3=5(B-9) | | -2x-1=s | | B=14-14 | | 3(k-5)-2(k+1)-13=-24 | | -2x-6+3x=10 | | 3x^2-.75-90=0 | | f(x)=-x^2+2x+16 |